Unsteady nodal modeling of building ventilation networks. (1st February 2022) - Esber, Ali; Faure, Xavier; Demouge, François; Wurtz, Etienne; Rouchier, Simon
Abstract: Ventilation network design and analysis are generally performed using nodal approaches (egg. 1 node for each zone) and quasi-static assumption. Thus, inertia effects of ducts are neglected as well as any possible acoustic resonance that could occur in any internal volume. These effects might be not as negligible as one could think while studying particular transient boundary conditions. Wind effect, including its turbulence, even at relatively small velocity, windstorm impact, flow disturbance, imply internal pressure fluctuations that cannot be caught if quasi-static assumption is considered within nodal numerical models. Inertia effect is not automatically linked to compressible and resonance assumptions can be identified even in incompressible conditions. The present study aims to identify in which cases the quasi-static assumption can be made. Simple stepwise boundary conditions are applied on a simple configuration with one zone and two ducts. The MATHIS software, developed to analyze ventilation systems in buildings and chosen as the standard tool in the French context, is used for this study and validated under unsteady state for a single zone case. A new approach is proposed to build a unique graphical analysis from two groups of terms, being define using a dimensionless method. Its usage enables to highlight in which situation internal pressure resonance will happen and therefore helps the modeler to choose the correct assumptions for further simulations. Highlights: The quasi-static assumption relevancy. Detection of the frequency and internal resonance due to the boundary conditions. Non-dimensional study on the energy and mass balance equations. New approach to build a unique graphical analysis that can describe the internal fluctuations.